A Non-linear Stochastic Consols Yield Model Of Malaysia - Nur Syahirah Abd Munil; Norizarina Ishak; Ahmad Fadly Nurullah Rasadee; Abu Bakar Hasan (The Academy of Sciences Malaysia, 2024)
ASM Sci. J., Special Issue 6, 2019 for SKSM26, 9-14